2021
DOI: 10.1016/j.biopsych.2020.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Liability for Internalizing Versus Externalizing Behavior Manifests in the Developing and Adult Hippocampus: Insight From a Meta-analysis of Transcriptional Profiling Studies in a Selectively Bred Rat Model

Abstract: Background: For over 16 years, we have selectively bred rats to show either high or low levels of exploratory activity within a novel environment. These "bred High Responder" (bHR) and "bred Low Responder" (bLR) rats serve as a model for temperamental extremes, exhibiting large differences in many internalizing and externalizing behaviors relevant to mood and substance abuse disorders. Methods:Our study elucidated persistent differences in gene expression related to bHR/bLR phenotype across development and adu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(75 citation statements)
references
References 129 publications
9
65
1
Order By: Relevance
“…Our first goal was to confirm and extend findings from our recent bHR/bLR meta-analysis showing differential expression of microglial signaling genes in hippocampus [ 25 ]. qPCR measured expression levels of multiple genes within the classical complement cascade, including cascade components C1q and C3 , and the receptor molecule cd11b (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Our first goal was to confirm and extend findings from our recent bHR/bLR meta-analysis showing differential expression of microglial signaling genes in hippocampus [ 25 ]. qPCR measured expression levels of multiple genes within the classical complement cascade, including cascade components C1q and C3 , and the receptor molecule cd11b (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…In multiple laboratory assays, bLRs display increased anxiety- and depressive-like behaviors and reduced social exploration and proactive coping [ 3 ]. Several lines of evidence from our lab implicate the hippocampus as a critical brain region underlying bHR/bLR phenotypes [ 14 , 20 , 23 , 24 ], and a recent meta-analysis of transcriptional studies spanning multiple generations identified broadly divergent gene expression patterns within hippocampus [ 25 ]. Interestingly, microglia-related pathways emerged as one of the main functional candidates from this analysis, with bLR hippocampus exhibiting elevated expression of several key genes related to microglial activation and signaling [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trhr encodes the receptor for thyrotropin-releasing hormone (TRH); TRH-R1 knockout mice exhibited increased anxiety- and depressive-like behaviors (Zeng et al, 2007 ). Low levels of exploratory activity in novel environment rats which are highly inhibited and anxious, depressive-like behavior expressed low Trhr level in dentate gyrus where neural proliferation within the hippocampus (Birt et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Trhr encodes the receptor for thyrotropin-releasing hormone (TRH); TRH-R1 knockout mice exhibited increased anxietyand depressive-like behaviors (Zeng et al, 2007). Low levels of exploratory activity in novel environment rats which are highly inhibited and anxious, depressive-like behavior expressed low Trhr level in dentate gyrus where neural proliferation within the hippocampus (Birt et al, 2021).…”
Section: Target Scanmentioning
confidence: 99%